A Football Field Lost Every 45 Minutes: Evaluating Local Capacity to Implement Louisiana's Coastal Master Plan. Issue 3 (4th May 2017) - Knox, Claire Connolly
ABSTRACT: As Louisiana continues to experience substantial coastal wetland loss—at the rate of a football field every 45 min—and multiple disasters, state and federal officials struggle with implementing restoration plans in this highly productive ecosystem. The 2007 Louisiana Comprehensive Master Plan for a Sustainable Coast is the first large-scale restoration plan in the United States to incorporate hazard mitigation. However, there is no mandate for local governments to adhere to this plan. Building upon the planning quality and evaluation literature, this study analyzes comprehensive land use plans in Louisiana's coastal zone to systematically assess the quality of the plans within the context of a non-mandated, 50 billion large-scale state restoration plan. Results indicate a great disparity in plan quality; a majority of the local governments lack the capacity to implement the nonstructural programmatic elements of the state's plan. The study concludes with a discussion and recommendations for practice and future research.